Off-Grid Solar Powered Ground Cooling System Dataset ... - Wagner, Anna; Maakestad, Jon; Yarmak, Edward; Douglas, Thomas (Zenodo, 2021)
The need to maintain frozen ground stability in the Arctic and sub-arctic is a continuing challenge, particularly with climate warming across the region. One engineering solution to tackle this problem is using thermosyphons, an artificial ground cooling apparatus, to stabilize frozen ground. Passive thermosyphons function when the above ground condenser section is colder than the subsurface evaporator section. This occurs when the ambient air temperature is colder than the current subsurface ground temperature. Passive thermosyphons absorb thermal energy from subsurface ground layers and reject it to the atmosphere. As such, this passive technology augments natural ground cooling during cold winter months. Hybrid thermosyphons are capable of operating in both passive mode and active (powered refrigeration) mode. For remote locations the electrical requirements for active thermosyphons greatly limit their application. However, solar power is a promising means of providing an electrical source to operate ...